The relationship between phosphodiesterase 4D gene polymorphism and coronary heart disease - Yan, Laixing; Li, Ketao; Zhang, Weiwei; Shen, Chengji; Ma, Liping; Sun, Yu (Cellular and Molecular Biology, 2022)
Coronary atherosclerotic heart disease is one of the most common heart diseases that seriously endanger human health. The study found that intracellular second messenger CAMP plays an important role in inhibiting the proliferation and migration of vascular smooth muscle and the local inflammatory response at the damaged vessel. Phosphodiesterase 4D (PDE4D) can specifically degrade cAMP. The purpose of this article is to investigate the relationship between phosphodiesterase 4D gene polymorphism and coronary heart disease and the effect of phosphodiesterase 4D gene polymorphism on cardiovascular, using polymerase chain reaction-restriction fragment length polymorphism method (PCR-RFLP) was used to detect 50 patients with coronary heart disease (ACS group) and 100 patients who were diagnosed with coronary artery disease by coronary angiography at the same time as the control group (NC group). The results of the study showed that the frequencies of AA, AG, and GG genotypes in 150 samples were 25.67%, 54.66%, and 22.67%, respectively, which was consistent with Hard Weber's law (X = 2.186, P = 0.101). The distribution of GG genotype (18% vs. 27%), AA + AG genotype (85% vs. 74%), G (57% vs. 55%), A (43% vs. 45 %) There was no statistically significant difference in allele frequency (P <0.05). From this, it can be seen that the rs918592 polymorphism of the PDE4D gene is not associated with coronary heart disease.